DEVELOPMENT OF BIOLOGY LEARNING INSTRUCTIONAL TO INCREASE STUDENTS’ ACHIEVEMENT AND SELF-DIRECTED BY SCIENCE PROCESS SKILLS APPROACH - Armansyah Putra; Rudiana Agustini; Yuni Sri Rahayu (JURNAL PENA SAINS, 2017)
This research is aimed to develop biology learning materials in Junior High School for plants movement topic to increase students’ achievement and self-directed through Science Process Skill approach. This is development research refers to Kemp’s development model. The learning kit is taught in SMPN 1 Blega Bangkalan Madura for 28 students grade VIII employing science process skill approach. The research design uses One Group Pretest-Posttest and data is analyzed with the qualitative descriptive method. This research reveals that the implementation of learning kit is 83%, dominant student’s activities in 1st and 2nd learning process are observing (22% - 24%), most of the students have positive responses which are indicated by 99% of students expressing their like, the result of students’ learning mastery satisfies the classical criteria for 86%, the rate of students self-directed varies from 55,56% to 83,32%. Based on the data analysis, it can be concluded that the Development of Biology Learning Kit is feasible.Keywords: Achievement, Self-directed, Science Process skill approach.